Perspektif Hukum Islam Terhadap Zakat Inovatif Dalam Pemberdayaan Keluarga Sakinah: Studi Kasus di Kampung Zakat Terpadu Dusun Paluombo, Sumbersalak Kecamatan Ledokombo Kabupaten Jember Tahun 2024 - Fenita Ayuning Lestari Fenita Ayuning Lestari (el-Bait: Jurnal Hukum Keluarga Islam, 2024)
Zakat village 02 experiences several problems, including the large number of migrant workers and migrant workers in the hamlet, even the highest in Jember district and many children getting married at an early age. With the aim of researching Islamic legal perspectives on innovative zakat in empowering the Sakinah family. The method used is a qualitative approach with a descriptive type, data obtained by observation, interviews and documentation. The results of this research show very significant changes in the zakat village 02, Paluombo hamlet, including now 80% of the community prioritizes education, there are even many bachelor's degree graduates in the zakat village 02 and the people there are Sakinah families. This research has the implication that with the existence of zakat village 02 with various programs such as mothers' schools and fathers' schools and providing a lot of assistance and donations to the community, it will create a Sakinah family.